Post-polyploid diploidization and diversification through dysploid changes - Mandáková, Terezie; Lysak, Martin A (Current opinion in plant biology, 2018)
Whole-genome duplications are widespread across land plant phylogenies and particularly frequent in ferns and angiosperms. Genome duplications spurred the evolution of key innovations associated with diversification in many angiosperm clades and lineages. Such diversifications are not initiated by genome doubling per se. Rather, differentiation of the primary polyploid populations through a range of processes results in post-polyploid genome diploidization. Structural diploidization gradually reverts the polyploid genome to one functionally diploid-like through chromosomal rearrangements which frequently result in dysploid changes. Dysploidies may lead to reproductive isolation among post-polyploid offspring and significantly contribute to speciation and cladogenetic events.
Keywords: Reproduction; Evolution, Molecular; diploidie; Genome, Plant; polyploidie; genom rostlinný; rozmnožování; Polyploidy; Diploidy; molekulární evoluce